“Just The Way You Are”: Self-Compassion, Community Social Support & Self-Acceptance of Parents With Down Syndrome Children - Septania, Sovi; Ridhowati, Vicilia (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
Abstract Parents with down syndrome children often experience difficulties with self-acceptance of their child’s special needs. Parents cover up the child’s condition from society, alienate the child from social activities, do not facilitate with required therapy, and eventually impact general parenting given. Parents who moved by child need to open up to join a community with other parents with down syndrome children as a necessity for social support. Internally, parents who can accept the weaknesses and strengths of their children are one the characteristics of self-compassion. This study aims to analyze the impact of self-compassion and community social support on parents’ self-acceptance. Using quantitative research methods with Likert scales consists of all instruments (self-compassion, community social support, and self-acceptance scale). They are analyzed with multiple regression techniques and purposive sampling with 50 respondents involved. The results showed that self-compassion and community social support contribute to the self-acceptance of parents with down syndrome children by 52.8 % (p<0.01). Separately, community social support had a 39.9% impact, while self-compassion had a 43.9% impact on the self-acceptance of parents with down syndrome children. Keywords: down syndrome children; community social support; self-acceptance; self-compassionAbstrakOrang tua dengan anak down syndrome seringkali mengalami kesulitan dalam proses penerimaan diri terhadap kondisi anak. Tidak jarang orang tua menutupi kondisi anak dari lingkungan sosial. Orang tua yang mampu menerima segala kekurangan dan kelebihan anak menjadi salah satu ciri self-compassion. Selain itu, perasaan kesamaan situasi dengan orang tua lain yang memiliki anak down syndrome dalam sebuah komunitas memberikan rasa dukungan sosial. Penelitian ini bertujuan menganalisis pengaruh self-compassion dan dukungan sosial komunitas terhadap penerimaan diri orang tua dengan anak down syndrome. Instrumen penelitian menggunakan tiga skala jenis likert yaitu skala self-compassion, skala dukungan sosial komunitas dan skala penerimaan diri orang tua. Metode penelitian kuantitatif dengan teknik purposive sampling melibatkan 50 responden. Analisis hipotesis dengan regresi berganda. Hasil penelitian menunjukan self-compassion dan dukungan sosial komunitas berpengaruh terhadap penerimaan diri orang tua dengan anak down syndrome sebesar 52.8% (p < 0.01). Secara terpisah, dukungan sosial komunitas berpengaruh sebesar 39.3% dan self-compassion sebesar 43.9% terhadap penerimaan diri orang tua dengan anak down syndrome.Kata kunci: anak down syndrome; dukungan sosial komunitas; penerimaan diri; self-compassionAbstract Parents with down syndrome children often experience difficulties in the process of self-acceptance of their child’s special needs. Parents cover up the child’s condition from society, alienate child from social activities, do not facilitate with required therapy, eventually impact on general parenting given. Parents who moved by child’s need open to join community with other parents with down syndrome children as necessity for social support. Internally, parents who are able to accept weaknesses and strengths of their children are one of the characteristics of self-compassion. This study aims to analyze the impact of self-compassion, community social support to parents’ self-acceptance. Using quantitative research methods with likert scales consist of self-compassion, community social support and self-acceptance scale which analyzed with multiple regression technique and purposive sampling with 50 respondents involved. The results showed that self-compassion and community social support contribute to self-acceptance of parents with down syndrome children by 52.8 % (p<0.01). Separately, community social support had 39.9% impact, while self-compassion had 43.9% impact to self-acceptance of parents with down syndrome children.[A1]  Keywords: down syndrome children, community social support, self-acceptance, self-compassion  AbstrakOrang tua dengan anak down syndrome seringkali mengalami kesulitan dalam proses penerimaan diri terhadap kondisi anak. Tidak jarang orang tua menutupi kondisi anak dari lingkungan sosial. Orang tua yang mampu menerima segala kekurangan dan kelebihan anak menjadi salah satu ciri self-compassion. Selain itu, perasaan kesamaan situasi dengan orang tua lain yang memiliki anak down syndrome dalam sebuah komunitas memberikan rasa dukungan sosial. Penelitian ini bertujuan menganalisis pengaruh self-compassion dan dukungan sosial komunitas terhadap penerimaan diri orang tua dengan anak down syndrome. Instrumen penelitian menggunakan tiga skala jenis likert yaitu skala self-compassion, skala dukungan sosial komunitas dan skala penerimaan diri orang tua. Metode penelitian kuantitatif dengan teknik purposive sampling melibatkan 50 responden. Analisis hipotesis dengan regresi berganda. Hasil penelitian menunjukan self-compassion dan dukungan sosial komunitas berpengaruh terhadap penerimaan diri orang tua dengan anak down syndrome sebesar 52.8% (p < 0.01). Secara terpisah, dukungan sosial komunitas berpengaruh sebesar 39.3% dan self-compassion sebesar 43.9% terhadap penerimaan diri orang tua dengan anak down syndrome. Kata kunci: anak down syndrome, dukungan sosial komunitas, penerimaan diri, self-compassion [A1]Tambahkan kesimpulan secara singkat pada akhir abstrak